Assessment of the Similarities of Selected European Countries in Terms of Socio-Economic Diversity - Małgorzata GRZYWIŃSKA-RĄPCA (Communications of International Proceedings, 2020)
The purpose of the article was to separate groups of European countries taking into account measures of socio-economic development, i.e. the index of social development. The analysis also took into account features such as life expectancy, expected and average years of education, and gross national income per capita. The hypothesis was formulated that the data on socio-economic development adopted for analysis differentiate countries and may be the basis for creating groups of countries bringing together similar territorial units. The application of statistical multidimensional analysis methods has allowed the separation of statistically uniform clusters. The study showed that the measures adopted for analysis differentiate countries in terms of socio-economic development. The most developed countries: Austria, Belgium, Denmark, Finland, Germany, Luxembourg, the Netherlands, Sweden, Great Britain, and the least: Cyprus, Czech Republic, France, Greece, Italy, Malta, Portugal, Slovenia, Spain.
Keywords: HDI; Quality of Life; Socio-Economic Development; European Countries.